Evaluasi Pengelolaan Limbah B3 Dari Kegiatan Pertambangan Batubara di PT. X Kalimantan Timur - Frederica Karunia Sandodo Limbong Rare; Mohamad Rangga Surur (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Mining activities are positive but havethe potential to cause damage and environmental degradation, one of which is due to hazardous and toxic waste generated. Producers of B3 waste must be responsible for the waste generated in accordance with applicable regulations but there are still many who neglect this responsibility so that the Company PerformanceRating Assessment Program (Proper) is made. This research was conducted by evaluating the management of B3 waste at PT. X with the Proper ChecklistEvaluation Form. This research methodology iscarried out by identifying the types of B3 waste generated and evaluating B3 waste management using the Guttman Scale by comparing the existing situation with the PROPER Checklistthen calculating the presentation of the level of conformity. The results of the study based on the results of evaluations and observations on the evaluation of B3 waste management at PT.X from 6 assessed implementations all get an %Actual Score of100%. So ,it can be concluded that the B3 waste management system at PT.X is in accordance with applicable regulations